2008
DOI: 10.1080/10408440802237664
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Involved in Cardiac Sensitization by Volatile Anesthetics: General Applicability to Halogenated Hydrocarbons?

Abstract: An increased sensitivity of the heart to catecholamines or cardiac sensitization is a recognized risk during acute human exposure to halogenated hydrocarbons used as solvents, foam-blowing or fire-extinguishing agents, refrigerants, and aerosol propellants. Although cardiac sensitization to such "industrial" halocarbons can result in serious arrhythmia and death, research into its mechanistic basis has been limited, whereas the literature on volatile anesthetics (e.g., halothane, chloroform) is comparably exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 253 publications
(268 reference statements)
0
21
0
Order By: Relevance
“…In this study, workers exposed to organic and halogenated solvents too. Another study showed the mechanisms involved in cardiac sensitization by halogenated hydrocarbons . Researchers demonstrated the fatal cardiac arrhythmia after repeated exposure to halogenated hydrocarbons …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, workers exposed to organic and halogenated solvents too. Another study showed the mechanisms involved in cardiac sensitization by halogenated hydrocarbons . Researchers demonstrated the fatal cardiac arrhythmia after repeated exposure to halogenated hydrocarbons …”
Section: Discussionmentioning
confidence: 99%
“…Researchers studied on the cardiac toxicity of the organochloride solvent trichloromethane . Other study showed the mechanisms of cardiac sensitization caused by volatile anesthetics …”
Section: Introductionmentioning
confidence: 99%
“…22 All inhaled agents sensitize the myocardium to catecholamines, which could potentiate the dysrhythmogenic effects of cocaine. Inhaled agents also have bronchodilating properties, which can be beneficial as cocaine use can lead to bronchospasm, especially in patients with asthma.…”
Section: Managementmentioning
confidence: 99%
“…Exposure causes significant higher amount of epinephrine release than the control group [66] and an increased sensitivity of the myocardium to epinephrine [64,67]. Furthermore, electrolyte imbalance, cardiac biomarkers, and oxidative stress markers were significantly affected and can cause damage to cardiomyocytes [66].…”
Section: Inhalent Abusementioning
confidence: 99%